2021
DOI: 10.2147/dmso.s291674
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Poor Plasma Glucose Maintenance in Type II Diabetic People with Ophthalmic Complication: The Case of Dessie Hospitals in Ethiopia

Abstract: Background: Diabetes mellitus, the commonest metabolic disorder, leads to cardiovascular diseases, neurological problems, kidney injury, and visual disturbances. Such complications can be prevented by maintaining plasma glucose level in the normal range, including ophthalmic complications. Hence, this study intended to pinpoint predictors of poor plasma glucose maintenance in type II DM people with ophthalmic complication. Methods: We conducted a cross-sectional survey using simple random sampling approach to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…This result was similar to that of the study conducted in Dessie, Ethiopia. The possible justification for this association is that an increment in the level of hyperglycemia or having poor glycemic control can increase the onset and rate of progression of diabetic retinopathy, which leads to visual impairment [ 19 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result was similar to that of the study conducted in Dessie, Ethiopia. The possible justification for this association is that an increment in the level of hyperglycemia or having poor glycemic control can increase the onset and rate of progression of diabetic retinopathy, which leads to visual impairment [ 19 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The length of disease was found to be the most commonly reported predictor of poor glycemic control (n = 12 studies) [ 22 , 25 , 26 , 27 , 30 , 31 , 32 , 35 , 37 , 38 , 39 , 40 ], whereas dietary habits were the second most commonly reported independent predictor of poorly controlled glucose levels (n = 8) [ 22 , 25 , 26 , 31 , 32 , 35 , 39 , 40 ]. Patients' sex (n = 10 studies) [ 21 , 25 , 29 , 30 , 31 , 32 , 33 , 36 , 37 , 38 ] and age (n = 7 studies) [ 21 , 25 , 31 , 32 , 35 , 37 , 38 ] were found to be predictive of glycemic control among biologic variables.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported that alcohol use was also associated with glycemic control [ 21 , 25 , 31 ], while two articles stated khat chewing [ 31 , 33 ] as a predictor of glycemic control. The most commonly reported socio-demographic variable is the educational status (n = 7 studies) [ 22 , 25 , 27 , 31 , 33 , 37 , 40 ], whereas residency [ 26 , 27 , 31 ] and employment status [ 22 , 34 ] were reported by three and two papers, respectively, as predicting glycemic control. Body mass index was reported by six authors [ 22 , 30 , 31 , 33 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations